An analysis of technical oral presentation anxiety in English among engineering students in Universiti Malaysia Pahang - Noor Raha, Mohd Radzuan (2013)
This main aim of this study was to analyze the anxiety experienced by engineering students in delivering effective technical oral presentations (TOP) in English in the context of chemical engineering education. It also investigated the factors that may have contributed to the students' feelings of anxiety. This study draws on the Social Cognitive Theory (Bandura, 1986), Processing Efficiency Theory (Eysenck & Calvo, 1992) and the Recursive Framework of Anxiety, Cognition and Behaviour (Macintyre, 1995) in discussing engineering students' technical oral presentation anxiety. In addition, the concept of Communication Apprehension (McCroskey, 1982b) was used as a basis in further understanding the anxiety experienced by the students in technical oral presentation and oral communication in English as a second language (ESL). This case study used a mixed method sequential explanatory approach proposed by Creswell (2003). Two questionnaires were used in this study: (1) an adapted version of Personal Report of Public Speaking Anxiety (PRPSA-34) (Richmond & McCroskey, 1998) questionnaire and (2) the Personal Report of Communication Apprehension (PRCA-24) (McCroskey, 1982a) questionnaire. Other instruments used were semi-structured interviews and document analysis. The sample comprised 135 final year engineering students and 6 lecturers from the Faculty of Chemical and Natural Resources Engineering (FCNRE) in Universiti Malaysia Pahang (UMP) as well as 7 industry personnel from chemical-related industries. Results showed that almost half of the respondents ( 46.7%) experienced high and moderately high anxiety in delivering technical oral presentations in English. Results also showed that majority of the respondents (73.3%) reported feeling moderately apprehensive in communicating orally in English and most respondents were highly anxious when giving speeches in public. Statistical analysis shows a negative weak correlation between the students' levels of TOP anxiety and their URPII final oral presentation scores. Results also showed that the students scored high marks in their URPII final oral presentation assessment even though most of them were reported to experience high and moderately high anxiety in the presentations. Six student focus group interviews and individual interviews with the panel of evaluators were also conducted. Findings revealed both similar and different perceptions of factors that affected students' TOP anxiety. Both groups perceived limited technical knowledge, panel of evaluators and barriers in students' English language to be major sources that impacted students' anxiety. However, factors such as lack of presentation skills and inadequate preparations were the two factors emphasized by the evaluators but not pointed out by the students. The students, on the other hand, perceived unhelpful supervisors, time constraints and having negative attitudes towards technical oral presentations as factors that affected their feelings of anxiety. This study extends previous research by including the findings from the students' actual experience in delivering individual technical oral presentations (TOP) in the field of English for Specific Purposes (ESP). Furthermore, an in-depth investigation on the sources of anxiety also contributes to understanding the anxiety experienced through the perspectives of both students and the evaluators.